Developing the organizational culture according to the implications of knowledge management trust - Paddy, Abbas Akle; Yasser, Imad Kadem (International Journal of Psychosocial Rehabilitation, 2020)
Organizational culture plays a prominent role in achieving the requirements of the study side, and this is often the result of the amount of real knowledge of reality, which extends from the amount of scientific achievement of the person and this correlation is direct whenever there is scientific knowledge, the more culture in society, and in the light of the results we concluded that the person Have a scientific follow-up able to explain the vocabulary more clearly than others and this talk documents the nature of the direct relationship between organizational culture and the amount of scientific knowledge.